Chapter 6. Cole Crop Production - Bonnie Wells; Hugh A. Smith; Lincoln Zotarelli; Peter J. Dittmar; Nicholas S. Dufault; Johan Desaeger; Qingren Wang (EDIS)
Chapter 6 of the Vegetable Production Handbook.